Evaluación nutricional y físico química de mezcla de pepino (cucumis sativus l.) y cedrón (aloysia triphylla) como base de una bebida funcional. - Paucar Peñaranda, Angélica Soledad (2015)
This study evaluated nutritional components and physical chemical mixing cucumber (Cucumis sativus L.) and lemon verbena (Aloysia triphylla) as the basis of a functional beverage. The results showed that the amount of vitamin C present in the mixtures is minimal compared to the recommended dose for FAO, regarding the evaluation of physical and chemical parameters determined that all mixtures meet required by the INEN 2337 standard: 2008. In addition to evaluating nutritional components and physical chemical antioxidant capacity C1 and C2 mixtures were studied through inhibition of DPPH radical, the IC50 value (half maximal inhibitory concentration) in C1 was 143.05 ug / ml and C2 was of 144.91 ug/mL, in percent inhibition of DPPH radical it was 27.38 and 36.09 respectively at a wavelength of 517 nm and presence bioactive compounds identified as flavonoids, tannins and saponins which tested positive for flavonoids in all mixtures.